2012
DOI: 10.1007/s10059-012-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Polarity of Protein Trafficking by Phosphorylation

Abstract: The asymmetry of environmental stimuli and the execution of developmental programs at the organism level require a corresponding polarity at the cellular level, in both unicellular and multicellular organisms. In plants, cell polarity is important in major developmental processes such as cell division, cell enlargement, cell morphogenesis, embryogenesis, axis formation, organ development, and defense. One of the most important factors controlling cell polarity is the asymmetric distribution of polarity determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 72 publications
0
58
0
Order By: Relevance
“…Based on the remarkable conservation of kinase domains in the CRK family, it is tempting to speculate that in analogy to the AGC kinases PID, WAG1, WAG2, and D6PK (reviewed in Ganguly et al, 2012), CRKs might contribute to cell type-specific phosphorylation of specific residues in hydrophilic loops of certain PINs and thereby regulate their polar membrane recycling. Thus, homologous members of the CRK family might perform overlapping cell type-specific functions, which could explain the relatively mild developmental effects of the crk5-1 mutation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the remarkable conservation of kinase domains in the CRK family, it is tempting to speculate that in analogy to the AGC kinases PID, WAG1, WAG2, and D6PK (reviewed in Ganguly et al, 2012), CRKs might contribute to cell type-specific phosphorylation of specific residues in hydrophilic loops of certain PINs and thereby regulate their polar membrane recycling. Thus, homologous members of the CRK family might perform overlapping cell type-specific functions, which could explain the relatively mild developmental effects of the crk5-1 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, endocytosis of PIN2 from the apical membrane is inhibited by brefeldin in gln1 mutant roots, suggesting that the apical endocytosis pathway is either dependent on or coregulated with the BFA-sensitive GNOM-dependent basal recycling pathway (Teh and Moore, 2007). Recently, Zhang et al (2010) identified two PID-independent phosphorylation sites in the hydrophilic loop of PIN1, which indicates that in addition to already known classes of AGCs (Ganguly et al, 2012), other protein kinases might also be involved in cell type-specific localization of some of the PINs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Three major families of auxin transporters have been identified: AUXIN-RESISTANT1 (AUX1)/AUX1-LIKEs for auxin influx and PIN-FORMED proteins (PINs) and several ATP binding cassette B/P-glycoprotein members for auxin efflux. PINs are particularly important for directional auxin transport and local auxin gradient formation because they localize asymmetrically in the plasma membrane (PM) and dynamically change their intracellular distribution in response to developmental and environmental signals (Grunewald and Friml, 2010;Ganguly et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is noteworthy that the pleiotropic effects of are1-1 are reminiscent of pin2 loss-of-function mutant Luschnig et al, 1998;Muller et al, 1998;Stepanova et al, 2007;Swarup et al, 2007;Utsuno et al, 1998), suggestive of close functional relationship between ARE1 and PIN2. It will be of great interest to test whether ARE1 is involved in posttranscriptional regulation of PIN2 that includes cell-type specific polar localization, stability, endocytosis and activity (Ganguly et al, 2012;Kleine-Vehn and Friml, 2008). An alternative possible mode of action of are1-1 is that it might change the cell-typespecific expression of auxin transporters other than PIN2.…”
Section: Discussionmentioning
confidence: 99%